The collected writings of J.N. Darby ; v. 14 - Darby, John Nelson, 1800-1882 (Kingston-on-Thames, UK Stow Hill Bible and Tract Depot, 1957)
Contents : v. 14 : Ecclesiastical no. 3
Brethren writer.
Keywords: Brethren movement -- historical writings